Immediate and sustained terminal complement inhibition with ravulizumab in patients with anti-aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder - Ortiz, Stephan; Pittock, Sean J.; Berthele, Achim; Levy, Michael; Nakashima, Ichiro; Oreja-Guevara, Celia; Allen, Kerstin; Mashhoon, Yasmin; Parks, Becky; Kim, Ho Jin (Frontiers in Neurology, 2024)
Objective To assess the pharmacokinetics and pharmacodynamics of the long-acting terminal complement 5 (C5) inhibitor ravulizumab in adults with anti-aquaporin-4 antibody-positive (AQP4+) neuromyelitis optica spectrum disorder (NMOSD) in the phase 3, open-label CHAMPION-NMOSD trial (NCT04201262). Methods Patients aged 18 years or older received a weight-based intravenous loading dose of ravulizumab (2,400–3,000 mg) on day 1, followed by weight-based maintenance doses (3,000–3,600 mg) on day 15 and once every 8 weeks thereafter. Pharmacokinetic assessments were maximum observed concentration (Cmax, assessed at the end of the infusion) and concentration at the end of the dosing interval (Ctrough, assessed before dosing) for ravulizumab. Pharmacodynamic assessment was time-matched observed free C5 concentration in serum up to 50 weeks. Results The pharmacokinetic/pharmacodynamic analysis included 58 patients treated with ravulizumab. Serum ravulizumab concentrations at or above the therapeutic threshold (175 μg/mL) were achieved in all patients after administration of the first dose and maintained for 50 weeks. At week 50, the mean (standard deviation) Cmax (n = 51) and Ctrough (n = 52) were 1,887.6 (411.38) and 764.4 (217.68) μg/mL, respectively. Immediate and complete terminal complement inhibition (free C5 serum concentrations < 0.5 μg/mL) was achieved by the end of the first ravulizumab infusion and sustained throughout the treatment period. No treatment-emergent antibodies to ravulizumab were observed. No impact on ravulizumab pharmacokinetics was seen for age, sex, race, hematocrit, hemoglobin, markers of renal and liver impairment, or medications commonly used by patients with NMOSD. Body weight and BMI were significant covariates of ravulizumab pharmacokinetics. Conclusions Serum ravulizumab concentrations were maintained above the therapeutic threshold in all patients through 50 weeks of treatment. Ravulizumab achieved immediate and complete terminal complement inhibition that was sustained throughout the treatment period in adults with AQP4+ NMOSD.